The rite of passage of becoming a humanitarian health worker: experiences of retention in Sweden - Sara Albuquerque; Anneli Eriksson; Helle M. Alvesson (Global Health Action, 2018)
Background: Low retention of humanitarian workers poses constraints on humanitarian organisations’ capacity to respond effectively to disasters. Research has focused on reasons for humanitarian workers leaving the sector, but little is known about the factors that can elucidate long-term commitment. Objective: To understand what motivates and supports experienced humanitarian health workers to remain in the sector. Methods: Semi-structured interviews were conducted with 10 experienced nurses who had been on at least three field missions with Médecins Sans Frontières Sweden. Interviews explored factors influencing the decision to go on missions, how nurses were supported and how they looked back on those experiences. Transcripts were analysed through content analysis informed by van Gennep’s concept of ‘Rite of Passage’, combined with elements of the self-determination theory. Results: The findings indicate that their motivations and how nurses thought of themselves, as individuals and professionals, changed over time. For initiation and continued engagement in humanitarian work, participants were motivated by several personal and professional ambitions, as well as altruistic principles of helping others. When starting their first humanitarian missions, nurses felt vulnerable and had low self-esteem. However, through experiencing feelings of autonomy, competence and relatedness during missions, they underwent a process of change and gradually adjusted to new roles as humanitarian health workers. Reintegration in their home community, while maintaining the new roles and skills from the missions, proved very challenging. They individually found their own ways of overcoming the lack of social support they experienced after missions in order to sustain their continuation in the sector. Conclusions: The findings highlight the importance of social environments that facilitate and support the adjustment of individuals during and after field missions. Learning from positive examples, such as nurses with several years of experience, can strengthen strategies of retention, which can ultimately improve the delivery of humanitarian assistance.